Pride and prejudice - Weldon, Fay; Austen, Jane ([S.l.] : British Broadcasting Corporation)
When the charming and kindly young Mr. Bingley moves to the neighbourhood, there is great excitement in the Bennet family. Jane, the eldest of five Bennet dauthers seems to have captured the heart of the wealthy young man. But when his friend, the haughty Mr. Darcy finds himself attracted to Elizabeth, the next sister, the tribulations of the Bennet family have only just begun....
Cast: Elizabeth Garvie, David Rintoul Moray Watson
Keywords: Motion pictures; Social aspects; Love